Harnessing Alpine Himalaya for In-situ Conservation of Critically Endangered Medicinal Plant: Dactylorhiza Hatagirea (D.Don) Soo - Bhardwaj, Meenakshi; Chauhan, N. S.; Kandari, L. S. (Indian Forester, 2013)
No Abstract